Improving the student learning experience through the student-led implementation of interactive features in an online open-access textbook - Sharma, Tanya; Lukose, Rini; Shiers-Hanley, Jessica E.; Hinic-Frlog, Sanja; Laughton, Simone (International Journal for Students as Partners, 2021)
This case study highlights the work of Students as Partners (SaP) as a balanced approach for implementing and evaluating an online open-access textbook in introductory animal physiology at the University of Toronto Mississauga. Started in 2017 with an eCampus Ontario grant, the project involved undergraduate and graduate students developing and improving an open-access e-textbook to support student learning in a second-year undergraduate introductory animal physiology course. This case study focuses on the 2019–2020 academic term and the work of two undergraduate students working alongside faculty and two librarians. As part of their research, the partners consulted the literature and gathered feedback from students taking the course in which the open e-textbook was used. Student partners added updates and new interactive features to create a more engaging educational resource to support student learning. The partners also reflected on their role in the open educational resource development process.